Contemporary Approaches to Breast Cancer Management: An Evidence Synthesis Guiding Clinical Practice and Patient Care. - J. Suliman, Naseralla; O. Al-Jahany , Marei; A. Moftah , Mohamed; F. Alhouni , Tarek (Benghazi University Medical Journal, 2025)
Background: Breast cancer remains the most frequently diagnosed cancer globally, though its management varies significantly across regions. This systematic review integrates recent evidence across six domains to delineate best practices for comprehensive care. Methods: A systematic literature search was conducted across MEDLINE, Embase, Cochrane Library, Web of Science, and CINAHL (2010–2024), in line with PRISMA 2020 reporting standards. Eligible studies were screened by two reviewers. Quality was assessed using validated tools appropriate to study design, including Cochrane RoB 2.0, Newcastle-Ottawa Scale, AMSTAR-2, and AGREE II. Evidence was synthesized narratively and appraised using the GRADE framework. Results: Key advances include the application of molecular profiling in tailoring therapy, treatment de-intensification for selected low-risk groups, escalation for aggressive subtypes, and improved multidisciplinary decision-making. Hypofractionated radiotherapy has shown comparable efficacy with reduced side effects, while genomic testing helps identify patients who can safely avoid chemotherapy. Targeted therapies have substantially improved outcomes in specific subgroups. Unique strategies are needed for elderly, male, and pregnant patients, and oligometastatic disease is increasingly approached with curative intent. Conclusion: Precision medicine has redefined breast cancer treatment, emphasizing individualized and integrated multidisciplinary strategies. Implementation frameworks that minimize disparities and maximize both survival and quality of life outcomes are necessary to put this evidence into practice.